PENGARUH BUDAYA ORGANISASI DAN JOB INSECURITY TERHADAP BURNOUT KARYAWAN MILLENIAL DI CV. MAPAN - Devika Cherly Putrihadiningrum; Ida Aju Brahmasari; Ida Aju Brahma Ratih (STIE Mahardhika, 2021)
Millennials have active and creative characters, including in choosing jobs. They choose jobs that are attractive, according to their competencies, provide high income and have the opportunity to develop their careers. Competition in the world of work does not always provide opportunities for everyone to get a job according to their passion and competence. Therefore, it is not uncommon for an employee, including millennial employees, to end up receiving a job that is not in accordance with his expectations and finds it difficult to adapt to the culture of the company where he or she works. This situation can hinder his or her performance. Low performance may cause an employee to face job insecurity and work stress. In every job there is the possibility of work stress, which, if not addressed, may lead to burnout. This study aims to prove and analyze the influence of organizational culture and job insecurity on millennial employee burnout of CV. Mapan Jaja in Surabaya. This research was conducted on millennial employees at CV. Mapan Jaya which has eleven branches in Surabaya with 428 employees. Using purposive multistage sampling, 156 respondents aged 11-30 years were determined. Results of the study prove that organizational culture and job insecurity have a significant effects on burnout of employees of CV. Mapan Jaya in Surabaya.